A clinical evaluation of the Janus Web Application, a software screening tool for drug-drug interactions. - Mannheimer B; Ulfvarson J; Eklöf S; Bergqvist M; von Bahr C (European Journal of Clinical Pharmacology, 2008)
PURPOSE: To evaluate the clinical relevance of the Janus Web Application (JWA) in screening for potential drug-drug interactions (DDIs). METHODS: One hundred and fifty patients taking two drugs or more were studied. Potential DDIs were identified by the JWA. Interviewing the patient and looking into his/her medical records provided complementing information. A clinical pharmacologist judged which potential DDIs were clinically relevant. Potentially relevant DDIs identified by the JWA were then correlated with clinically relevant DDIs. RESULTS: A total of 150 significant potential DDIs were found. Sixteen percent (24/150) were judged to be clinically relevant. CONCLUSIONS: A very small proportion of DDIs was considered clinically relevant in the specific clinical context. To optimise the software's user-friendliness, the following points need to be considered: the possibility of eliminating trivial potential DDIs, individualising drug alerts, and providing written information, accessible via a hyperlink.